Physical and mechanical properties of bamboo-filled epoxy composites from selected Malaysian bamboo - Khani, Parnia Zaki (2016)
Natural plant fibre composites have been developed for the production of a variety of industrial products, with benefits including environmental protection. Bamboo fibre materials have attracted broad attention as reinforced polymer composites due to their environmental sustainability, mechanical properties, and recyclability. Bamboo culm is a fast growing plant and grows abundantly in Asia, South America, and other diverse climates. Peninsular Malaysia, as a tropical region, has approximately 59 bamboo species from approximately seven genera. From the microstructure analysis of a bamboo culm, it has been revealed that the distribution and the percentage of fibre in wall area varies from bottom to top portion.Therefore, the mechanical and physical properties of a bamboo species are different from bottom to top portion. In this regard, this research aims to investigate four different Malaysian bamboo species, namely Gigantochloa scortechinii (GS),Gigantochloa levis (GL), Dendrocalamus asper (DA), and Dendrocalamus pendulus (DP) divided into three portions (bottom (B), middle (M) and top (T)). It should be noted that the anatomical structure of bamboo species is characterized by vascular bundles, and mechanical, physical and thermal properties of single fibres.In order to extract short fibres from bamboo species a systematic method is proposed, including a combination of alkaline treatment (2% and 4% NaOH) and grinding procedure. In this method, short bamboo fibres with the size of 150μm were distributed in epoxy resin and their mechanical and physical properties were investigated separately. The results show that the mechanical and physical properties of bamboo culms vary between species and along the culm. The results obtained from single fibre tests revealed that the bottom portion of every species possesses the highest mechanical properties. Dendrocalamus asper (DA) as a single fibre showed the highest Young’s modulus, strength and thermal stability in comparison with other species. The most optimum mechanical and physical properties of the bamboo fibre-reinforced epoxy composite obtained with a fibre content of 10 wt.%. The mechanical properties of DA, GS and GL fibre reinforced composites decreased by increasing the percentage of alkalization whereas, the properties of DP composites improved through mercerization, where the 2% of NaOH increased the values even higher than 4% alkaline. The physical properties of DP and GS fibre reinforced epoxy composite improved by 2% sodium hydroxide while DA composite by 4% alkaline. In contrast, untreated GL fibre reinforced composite demonstrated the best mechanical and physical properties, especially at the bottom and the middle portions. The mechanical properties of neat epoxy improved by adding short bamboo fibres. The overall results illustrate that short fibre of DP and GL species present the most suitable option for the purpose of composite production.